Dynamics of state price densities - Wolfgang Karl Härdle; Zdeněk Hlávka (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2005)
State price densities (SPD) are an important element in applied quantitative finance. In a Black-Scholes model they are lognormal distributions with constant volatility parameter. In practice volatility changes and the distribution deviates from log-normality. We estimate SPDs using EUREX option data on the DAX index via a nonparametric estimator of the second derivative of the (European) call price function. The estimator is constrained so as to satisfy no-arbitrage constraints and it corrects for intraday covariance structure. Given a low dimensional representation of this SPD we study its dynamic for the years 1995-2003. We calculate a prediction corridor for the DAX for a 45 day forecast. The proposed algorithm is simple, it allows calculation of future volatility and can be applied to hedging exotic options.
Keywords: 330; option pricing; state price density estimation; nonlinear least squares; confidence intervals